2022
DOI: 10.1002/adem.202270026
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Mechanical Plane Shifting in Bending Elastomer Film Revealed by Quantification of Internal Strain

Abstract: Neutral mechanical plane (NMP) position of a bending elastomer film is experimentally identified by internal strain analysis utilizing reflection of a cholesteric liquid crystal elastomer sensor as described in article number http://doi.wiley.com/10.1002/adem.202101041 by Atsushi Shishido, Norihisa Akamatsu and co‐workers. The internal strain analysis revealed NMP shifting during elastic bending. Quantification of the NMP shifting in the bending elastomer film enables us to design a flexible electronic device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…These blue shifts were due to the decrease in the helical pitch of the CLCE sensors, indicating that out-of-plane compression was induced in the bent bilayer PDMS films, as reported previously (see insets). 27,28,30,31 The bent bilayer PDMS films containing the CLCE sensor were confirmed to be tightly bonded, even at 50% applied strain. Figure 5c,d shows the reflection spectra of the S 500 H 1000 and H 500 S 1000 films, respectively.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…These blue shifts were due to the decrease in the helical pitch of the CLCE sensors, indicating that out-of-plane compression was induced in the bent bilayer PDMS films, as reported previously (see insets). 27,28,30,31 The bent bilayer PDMS films containing the CLCE sensor were confirmed to be tightly bonded, even at 50% applied strain. Figure 5c,d shows the reflection spectra of the S 500 H 1000 and H 500 S 1000 films, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…A blue shift was observed in the reflection spectra of the S 750 H 750 film, whereas a slight red shift and subsequent blue shift were observed in the reflection spectra of the H 750 S 750 film. The red shift represents the increase in the helical pitch of the CLCE sensors induced by the out-of-plane tension (see insets) . Through the reflection spectra measurement with the CLCE sensor, we found that, even at the same interface positions, the reflection wavelength shifts, acting as an indicator of the interfacial bending strain, were different.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations